Semantic and Syntactic Processing During Comprehension: ERP Evidence From Chinese QING Structure - Yang, Siqin; Cai, Yeyi; Xie, Wen; Jiang, Minghu (Frontiers in Human Neuroscience, 2021)
Previous studies used BA and BEI structures as stimuli to infer that syntax-first models were not applicable in Chinese. However, there were inconsistent results of both within same structures and between different structures. Since sentence structures of stimuli were noncanonical as well as lacking wide representativeness in Chinese, we examined the processing mechanism of a more representative structure in Chinese, QING (QING +NP1+V+NP2) structure in the current study. Four conditions, including correct sentences (CORRECT), semantic violated sentences (SEMANTIC), syntactic violated sentences (SYNTACTIC) and combined violated sentence (COMBINED), were composed by manipulating the V between NP1 and NP2. Results with respect to three types of violation were as follows. In the initial phrase (100-300 ms), there existed an interaction between SEMANTIC consistency and SYNTACTIC category. In the intermediate phrase (300-500 ms), the interaction continued with similar negative waves evoked by three types of violated sentences. In the final phrase (500-700 ms), both SYNTACTIC or COMBINED evoked obvious negative waves instead of P600. The current research of Qing structure provided new evidence for the processing mechanism of Chinese sentence patterns. Specifically, we found that interactive model rather than syntax-first model may apply to the processing of this specific structure of Chinese sentence and compared the results with those reported in previous studies that examined other types of sentence structure.